Repressive Dynamics and Political Subjectivities: the Case of Peniche Prison - Cardina,Miguel (2015)
This paper analyzes the experience of political prisoners in the final stages of theEstado Novo dictatorship. It uses the Peniche Fort prison as a case study, exploring the way in which political identities were defined, and even reinforced, throughout the struggle against coercive dynamics. Physical confinement, rules, isolation, surveillance, and punishment laid the foundations for a punitive structure that aimed to produce “docile bodies.” On the other hand, prisoners built up resistance strategies intended not only to escape the objective reality of incarceration, but also to assert their militant subjectivity. The article explores how ideological splits led to distinct cultures of protest and ways of experiencing everyday life inside the prison, whilst also revealing how prison life interacted with broader political dynamics.